2009
DOI: 10.1073/pnas.0903163106
|View full text |Cite
|
Sign up to set email alerts
|

Tracking lineages of single cells in lines using a microfluidic device

Abstract: Cells within a genetically identical population exhibit phenotypic variation that in some cases can persist across multiple generations. However, information about the temporal variation and familial dependence of protein levels remains hidden when studying the population as an ensemble. To correlate phenotypes with the age and genealogy of single cells over time, we developed a microfluidic device that enables us to track multiple lineages in parallel by trapping single cells and constraining them to grow in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 39 publications
1
89
0
Order By: Relevance
“…The designs reported previously can track trapped mother cells for only up to 18 h (24) and for up to eight divisions (25). Although another system could track the whole lifespan of trapped mother cells, the retention rate of these cells in the original traps over the time course was ∼40-60% (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The designs reported previously can track trapped mother cells for only up to 18 h (24) and for up to eight divisions (25). Although another system could track the whole lifespan of trapped mother cells, the retention rate of these cells in the original traps over the time course was ∼40-60% (26).…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic system designs for studying yeast aging have been reported previously (24)(25)(26); however, they did not permit assays of yeast replicative lifespan because they are unable to track the entire lifespan of mother cells due to the low efficiency in removing daughter cells. The designs reported previously can track trapped mother cells for only up to 18 h (24) and for up to eight divisions (25).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Weitz group trapped yeast cells in lines, and analyzed the fluctuations and patterns in protein expression within single cells over multiple generations. [17] The Li group developed a microfluidic device that retained mother yeast cells by PDMS (Polydimethylsiloxane) pillars. [18] They attached the yeast cells on a wall coated by avidin to track individual mother cells throughout their whole lifespan, and found that the aging of cells was characterized by an increased general stress and a progressive lengthening of cell cycle for the last few cell divisions.…”
Section: High Resolutionmentioning
confidence: 99%
“…18 Importantly, particles are arrayed with a perfect yield, making it a prime candidate technology for research with rare and precious cells, such as those harvested from biopsy samples. More recently, parallel arrays of trap structures and bypass channels have been used for tracking yeast 19 and human cell lineages. 20 In this contribution we introduce a cellular valving principle for use with a Tan and Takeuchi microfluidic architecture for highly efficient and reliable single cell coupling.…”
Section: Introductionmentioning
confidence: 99%